Changes of selected biochemical parameters of blood, densytometric and strength bones of rats under low frequency vibration - DAMIJAN, Z. (Archives of Acoustics, 2005)
The aim of the research is to analyze the changes of selected biochemical blood, densitometric parameters and bone strength of rats under exposure to low-frequency vibrations. Experiments were run on 30 Wistar rats randomly divided into three groups: the first group was first exposed to vibrations when rats were 20 days old: _20 - before puberty, the second group was subjected to vibrations from the 70-th day on: _70 - after reaching puberty, the third is the control group: _K. On the 145-th day the rats' _20 and _70 bones were subjected to biochemical examination, followed by densitometric and bone strength tests.